Being Good, Moral and Rational in a Context of Climate Change - Rosół, Piotr (ETHICS IN PROGRESS, 2016)
Climate change has become a popular topic with a strong presence in media, political, scientific and ethical debates. This raises a question as to why we are not acting in accordance with our knowledge and are unable to do enough to protect our future. The paper argues that the problem partly arises from a lack of philosophical reflection about relations between different aspects of our personalities. Those different aspects are presented based on the reflections of Thomas Nagel on good, moral, and rational ways of life. I claim that all three need to be taken into consideration in order to answer challenge raised by the environmental dangers we are facing.